The falsies effect: How this beauty trend falsely induces severe glaucoma - Sophia C. Bertot; Pooja Pendri; Elena Bitrian (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To bring awareness on how the false eyelash beauty trend can impact routine glaucoma evaluations. Observation: False eyelashes have the ability to induce pseudoptosis and visual disturbance complaints from patients. This translates to the patient care setting by inhibiting proper administration of Humphrey Visual Field analysis and portraying gross overestimations on patients’ glaucoma progression. Conclusions: Patients should be asked to remove false eyelashes prior to administering Humphrey Visual Field analysis or have their eyelids taped up to prevent obstruction of view during examination. Importance: Making medical management decisions based on a Humphrey Visual Field analysis completed on a patient wearing false eyelashes could lead to overly aggressive treatment on an otherwise healthy patient.